Inflation, Rupiah Exchange Rates, And Interest Rates On The Financial Performance Of State-Owned Banks For 2013-2022 Period - Justiro, Nur Iqbal; Irawati, Zulfa (Jurnal Ilmu Manajemen Advantage, 2023)
This study's overarching goal is to examine the impact of interest rates, inflation, and the value of the rupiah on the bottom line of state-owned banks from 2013 to 2022. One or more types of banking services are currently required by almost every sector in Indonesia that engages with monetary transactions. The macroeconomic circumstances have an effect on the rules that govern Bank Indonesia, and these regulations are applicable to all banks in Indonesia, which means that they have an effect on the processes that banks use to conduct their business. This research makes use of a quantitative technique, and it does so by collecting secondary data from Indonesian banks that are controlled by the state. In order to conduct the analysis of the data for this research, the approach of multiple linear regression was used. On the basis of the conclusions of this research, it seems that the ROA indicator is mostly unaffected by factors like as interest rates, inflation, and the currency rate of the Rupiah. When it comes to the calculation of the LDR indicator, the rates of inflation and interest, as well as the exchange rate of the Rupiah, all play a part. There exists a relationship between the CAR indicator and the rate at which the Rupiah is being exchanged. The CAR indicator, on the other hand, is not impacted by inflation in any way. At the same time, inflation, the rate of the Rupiah currency, and interest rates all have an impact on the functioning of the financial system. ROA, LDR, and CAR are the metrics that are used to quantify these characteristics. These metrics stand for capital adequacy, liquidity, and profitability in regard to one another.